INVOLVEMENT OF ALTIMETRY INFORMATION INTO THE IMPROVED PHOTOCLINOMETRY METHOD FOR RELIEF RETRIEVAL FROM A SLOPE FIELD - Yu. V. Kornienko; I. A. Dulova; N. V. Bondarenko (Radio Physics and Radio Astronomy, 2021)
Purpose: The paper discusses the possibility for increasing the planet’s surface relief retrieving accuracy with the improved photoclinometry method through the reference of the desired relief to the altimetry data. The general approach to solving the problem is proposed. The use of altimeters having both wide and narrow beam patterns are discussed, but the narrow beam pattern altimeter data is studied more in detail. The spatial resolution of the retrieved relief calculated with the improved photoclinometry method conforms to the one of the source images. Altimetry allows absolute reference to the surface heights and improves the accuracy of the relief determination.